Aims and Principles of the Criminal Trial: From Franz von Zeiller’s Zweck und Principien to Friedrich von Savigny’s Prinzipienfragen (Italian Review of Legal History, 2015)
A comparative analysis of Zeiller’s Zweck und Principien and of Savigny’s Prinzipienfragen provides useful information for shedding new light on the animated debates and attempts to reform in a liberal way the regulations of the deutscher gemeinrechtlicher Strafprozeß followed in most Mitteleuropean countries during the first half of the nineteenth century. The growing awareness that adjective law should both protect human rights and promote personal freedoms led in fact many important German jurists to declare for a radical reform of the inquisitorial system and of the traditional forms of carrying out criminal trials.
Keywords: Criminal Law; Inquisitorial procedures; German criminal law scholars; Austria; Prussia